1:12 + 2:41 + 1:10 = 4 hours 63 mins
5 Hours and 3 Mins
Answer:
C = (2,2)
Step-by-step explanation:
B = (10 ; 2)
M = (6 ; 2)
C = (x ; y )
|___________|___________|
B (10;2) M (6;2) C ( x; y)
So:
dBM = dMC
√[(2-2)^2 + (6-10)^2] = √[(y-2)^2 + (x - 6)^2]
(2-2)^2 - (6-10)^2 = (y-2)^2 + (x - 6)^2
0 + (-4)^2 = (y-2)^2 + (x - 6)^2
16 = (y-2)^2 + (x - 6)^2
16 - (x - 6)^2 = (y-2)^2
Also:
2*dBM = dBC
2*√[(2-2)^2 + (6-10)^2] = √[(y-2)^2 + (x - 10)^2]
4*[(0)^2 + (-4)^2] = (y-2)^2 + (x - 10)^2
4*(16) = (y-2)^2 + (x - 10)^2
64 = (y-2)^2 + (x - 10)^2
64 = 16 - (x - 6)^2 + (x - 10)^2
48 = (x - 10)^2 - (x - 6)^2
48 = x^2 - 20*x + 100 - x^2 + 12*x - 36
48 = - 20*x + 100 + 12*x - 36
8*x = 16
x = 2
Thus:
16 - (x - 6)^2 = (y-2)^2
16 - (2 - 6)^2 = (y-2)^2
16 - (-4)^2 = (y-2)^2
16 - 16 = (y-2)^2
0 = (y-2)^2
0 = y - 2
2 = y
⇒ C = (2,2)
ANSWER—46
Step-by-step explanation:
*All the angles in a triangle add up to 180 degrees.*
Let The wanted angle be x,
Then x+98+36=180. Solve for x.
Answer:
Yes
Step-by-step explanation:
Many students gets confused with these exponential problems, they often get misguided but understand that there is nothing to be confused of.
When you have a negative number, you just take the reciprocal of the whole exponent number.
What is a reciprocal?
Let's take an integer for example, let's take the number 3.
The reciprocal for 3 is (1/3)
Let's take an other number, let's take 2/3
The reciprocal for 2/3 is (3/2)
In conclusion, we just reverse the denominator and the numerator or just switch it.
We take 3 as (3/1) and that is the reason, the reciprocal would be (1/3)
Now, coming to the negative integers. Taking an example:
(2)⁻¹
This would be become (1/2¹) = (1/2)
Hence, the result of a negative integer is positive but would be a fraction.
Hope I helped!